CHALLENGES AND BENEFITS OF DIGITAL LEARNING: PERSPECTIVES FROM PROFESSORS AT A TWICE-DISPLACED UNIVERSITY DUE TO WAR - Semenov , Mykola (Studies in Comparative Education, 2024)
This study investigates the challenges and benefits of digital learning from the perspective of lecturers at Luhansk Taras Shevchenko National University, an institution that has been twice displaced due to military aggression. Over the past decade, the lecturers have experienced forced transformations in educational delivery, including a full year of distance learning in 2014, a transition from blended to traditional modes, and subsequent digital adaptations during the pandemic and ongoing military aggression. This unique experience provides insights into the irreversible digitalization processes occurring in higher education. Examining the views of lecturers with such exposure can form predictions about the future trajectory of universities. The research employed an online questionnaire distributed via the LimeSurvey platform to survey the academic staff. Key areas of inquiry included assessing lecturers’ readiness for digital learning, peculiarities of organizing digital learning at the institution, challenges encountered, utilization of digital tools, and perspectives on the future role of digital learning. The study findings highlighted the need to increase interactive and active teaching methods in digital formats, adapt learning content, and redefine the lecturer’s role as a facilitator while maintaining structured student-instructor interactions to ensure quality outcomes. A recommended hybrid model flexibly combines mixed formats, synchronous, and asynchronous interactions. The results indicate that lecturers’ mindsets have evolved through their experiences at twice-displaced university, fostering a new vision of the digital university paradigm.